PENERAPAN KODE ETIK DAN ETIKA PROFESI AKUNTAN PUBLIK DALAM MENGHADAPI TANTANGAN ERA DIGITAL - Eufemia Nunu; Veronika Leto Baga; Sariningsi Tanggu; Dionisisa Sawu; Fransiskus Suban Mawar (PT. Saha Kreasi Indonesia, 2025)
The digital era has brought significant changes to accounting practices, including the increasing use of technologies such as cloud-based accounting information systems, artificial intelligence (AI), big data, and audit automation. These advancements provide opportunities for public accountants to enhance the efficiency and accuracy of examinations, yet they also introduce new challenges in applying professional codes of ethics. This study aims to analyze how public accountants implement ethical principles—integrity, objectivity, professional competence and due care, confidentiality, and professional behavior—in responding to risks arising from digitalization, such as data security threats, technology-based information manipulation, and dependency on software. The research employs a literature review method by examining various journals, professional standards, and reports from accounting profession organizations. The findings indicate that applying ethical principles in the digital era requires public accountants to improve technological literacy, strengthen internal control systems, and maintain independence when using digital tools. Furthermore, commitment to professional ethics must be supported by updated regulations and practical guidelines to adapt to digital dynamics. Thus, ethical conduct remains a fundamental pillar in ensuring the quality, public trust, and credibility of public accountants amid ongoing digital transformation.